2007
DOI: 10.1038/oby.2007.332
|View full text |Cite
|
Sign up to set email alerts
|

First Nationwide Survey of Prevalence of Overweight, Underweight, and Abdominal Obesity in Iranian Adults

Abstract: The selection was conducted by stratified probability cluster sampling through household family members in Iran. Weight, height, and waist circumference (WC) of 89,404 men and women 15 to 65 years of age (mean, 39.2 years) were measured. The criteria for underweight, normal-weight, overweight, and Class I, II, and III obesity were BMI Ͻ18.5, 18.5 to 24.9, 25 to 29.9, 30 to 34.9, 35 to 39.9, and Ն40 (kg/m 2 ), respectively. Abdominal obesity was defined as WC Ն102 cm in men and Ն88 cm in women. Results: The age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
150
9
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(224 citation statements)
references
References 42 publications
40
150
9
16
Order By: Relevance
“…In agreement with other studies worldwide[1,24] and in Iran [7,9,25], our findings show that the prevalences of obesity and abdominal obesity in women are higher than men; gender differences in food intake, physical activity level and psycho-socio-economic status may be responsible for this difference. For example, results of a survey showed that Tehranian women consume more sweets and simple sugars [26].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other studies worldwide[1,24] and in Iran [7,9,25], our findings show that the prevalences of obesity and abdominal obesity in women are higher than men; gender differences in food intake, physical activity level and psycho-socio-economic status may be responsible for this difference. For example, results of a survey showed that Tehranian women consume more sweets and simple sugars [26].…”
Section: Discussionsupporting
confidence: 93%
“…In Iran, the prevalence of overweight and obesity in 2005 was reported to be 42.8% in men and 57% in women [7]; for 2015, the figures are predicted to be 54 and 74% respectively [8]. Studies have shown that the prevalence of abdominal obesity to range between 9.7 - 12.9% and 54.5 - 63.7% in Iranian men and women respectively [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, secular changes in increasing overweight/ obesity, especially in women, have been documented in these areas (9) . The present study suggests that while underweight is still the main nutritional problem among young children, it might be replaced by overweight as children grow to adolescence.…”
Section: Resultsmentioning
confidence: 99%
“…24 Thus, the high predictive power of WHR for incident CVD in our study population might be attributable to the high prevalence of sedentary lifestyle, especially in females. 25 In the INTER-HEART study, WHR was the strongest anthropometric predictor of myocardial infarction in both genders. 4 The superiority of WHR over WC could be related to HC, as the greater HC is inversely associated with CVD risk.…”
Section: Obesity Variables To Predict Cardiovascular Events F Hadaeghmentioning
confidence: 98%